2016
DOI: 10.14301/llcs.v7i1.325
|View full text |Cite
|
Sign up to set email alerts
|

Origins of heath inequalities: the case for Allostatic Load

Abstract: In an opening paper Delpierre et al. explore

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 82 publications
(102 reference statements)
3
25
0
Order By: Relevance
“…However, while the simplest form, the risk index, showed lower discriminatory power than the more complex functional forms, the results indicate that while there are some gains from choosing a functional form that is more complex than the simple index, the total gain is modest. Therefore, we argue that in certain circumstances in which survey-based research focuses on generalized concepts like allostatic load (Delpierre et al 2016a;Juster, McEwen, and Lupien 2010;McEwen 1998;Seeman et al 2001), our results validate such a parsimonious approach, at least for the set of CVD-related biomarkers under study here. A similar approach might seem appropriate if health inequalities with respect to objective indicators are the subject of investigation (Dowd and Zajacova 2010;Rosero-Bixby and Dow 2009), as an alternative to looking at risk differences for specific health issues, such as hbA1c for diabetes (Bennett, Guo, and Dharmage 2007;Rohlfing et al 2000).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, while the simplest form, the risk index, showed lower discriminatory power than the more complex functional forms, the results indicate that while there are some gains from choosing a functional form that is more complex than the simple index, the total gain is modest. Therefore, we argue that in certain circumstances in which survey-based research focuses on generalized concepts like allostatic load (Delpierre et al 2016a;Juster, McEwen, and Lupien 2010;McEwen 1998;Seeman et al 2001), our results validate such a parsimonious approach, at least for the set of CVD-related biomarkers under study here. A similar approach might seem appropriate if health inequalities with respect to objective indicators are the subject of investigation (Dowd and Zajacova 2010;Rosero-Bixby and Dow 2009), as an alternative to looking at risk differences for specific health issues, such as hbA1c for diabetes (Bennett, Guo, and Dharmage 2007;Rohlfing et al 2000).…”
Section: Discussionsupporting
confidence: 62%
“…Generally, there are two opposing approaches: On the one hand, a focus on very specific conditions like diabetes could warrant the use of one specific biomarker like hbA1c or C-reactive protein (CRP); for example, using hbA1c as a screening tool for undiagnosed diabetes (Bennett, Guo, and Dharmage 2007;Rohlfing et al 2000), or investigating the relationship between CRP and depressive symptoms (Hamer and Chida 2009). On the other hand, research can focus more on the overall wear and tear of the body as represented by the concepts of allostatic load (Delpierre et al 2016a;Juster, McEwen, and Lupien 2010;McEwen 1998;Seeman et al 2001) and biological age (Levine and Crimmins 2014), or on more specific CVD indices, including the well-known Framingham Heart Score (Lloyd-Jones et al 2004). In many applications it is difficult to find an explicitly theoretically driven framework for the implementation of biomarkers in survey research.…”
Section: Introductionmentioning
confidence: 99%
“…Important advances have been made in such areas as understanding the physiological mechanisms by which chronic stress associated with privation and insecurity impairs health, often with a long time lag between initial exposure and effect (Barboza Solís, Fantin, Kelly-Irving, & Delpierre, 2016;Barboza Solís et al, 2015;Gallo, Fortmann, & Mattei, 2014;McEwen, 2015;McEwen, 2012;Delpierre et al, 2016) and the multiple pathways by which reduced 'control over destiny', which may occur at the individual level but as a consequence of macro-scale economic and social processes, leads to negative health outcomes (Whitehead et al, 2016). In addition, the importance of environmental pollution as a contributor to the burden of noncommunicable disease, especially (although not only) in low-and middleincome countries, is belatedly being acknowledged (Vineis, Stringhini, & Porta, 2014;Fuller et al, 2018;Landrigan et al, 2018).…”
Section: Figure 1 a Tale Of A Sinking Stone?mentioning
confidence: 99%
“…The prolonged activation of compensatory physiological mechanisms can lead to a physiological ‘wear-and-tear’, termed allostatic load (AL) [ 9 , 11 13 ]. The AL model of chronic stress focuses on glucocorticoid dysregulation as part of a ‘network of allostasis’ involving autonomic, endocrine, metabolic, and immune mediators [ 14 , 15 ]. A variety of studies using measures of AL have suggested its association with numerous health outcomes and higher all-cause of mortality risk [ 16 ].…”
Section: Introductionmentioning
confidence: 99%